2023
DOI: 10.1001/jamaophthalmol.2023.2336
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Parenteral Nutrition Duration on Risk of Retinopathy of Prematurity

Abstract: ImportanceThe prognostic impact of parenteral nutrition duration (PND) on retinopathy of prematurity (ROP) is not well studied. Safe prediction models can help optimize ROP screening by effectively discriminating high-risk from low-risk infants.ObjectiveTo evaluate the prognostic value of PND on ROP; to update and validate the Digital ROP (DIGIROP) 2.0 birth into prescreen and screen prediction models to include all ROP-screened infants regardless of gestational age (GA) and incorporate PND; and to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…This study demonstrated an increased risk of ROP and a shortened time frame to initiation of ROP therapy in the PN group compared with those transitioned to enteral feeds. 13 When discussing enteral nutrition, exclusive Mothers' own milk (MoM) has demonstrated a lower incidence of ROP relative to formula-fed infants. 14 Long-chain polyunsaturated fatty acids LCPUFA are critical for the maturation of the brain and retina.…”
Section: Parenteral and Enteral Nutritionmentioning
confidence: 99%
“…This study demonstrated an increased risk of ROP and a shortened time frame to initiation of ROP therapy in the PN group compared with those transitioned to enteral feeds. 13 When discussing enteral nutrition, exclusive Mothers' own milk (MoM) has demonstrated a lower incidence of ROP relative to formula-fed infants. 14 Long-chain polyunsaturated fatty acids LCPUFA are critical for the maturation of the brain and retina.…”
Section: Parenteral and Enteral Nutritionmentioning
confidence: 99%